PENGARUH HARGA, BRAND AWARENESS, DAN KUALITAS PRODUK TERHADAP MINAT BELI TEH GAMBIR (STUDI KASUS KABUPATEN PAKPAK BHARAT) - Nurita Maha; Nurbaiti; Muhammad Ikhsan (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
This research aims to determine the influence of price, brand awareness and product quality on interest in buying Gambir tea (Pakpak Bharat Regency case study) either partially or simultaneously. The discussion in this research is related to marketing management. In this regard, the method used in this research is a quantitative method. The number of samples in this study was 97 people using the Chocran formula. The data collection techniques used are observation, documentation and questionnaires. The results of the partial research show that there is a negative and significant influence of price on interest in buying Gambir Tea with a calculated price t value of -8,530 > t table 1.666 with a significant value of 0.000 <0.05, so Ho1 is rejected and Ha1 is accepted. There is no influence of Brand Awareness on interest in buying Gambir Tea, with the calculated t value for the Brand Awareness variable 650 t table 1.666 with a significant value of 0.517 above 0.05, so Ho2 is accepted and Ha2 is rejected. There is a positive and significant influence of Product Quality on interest in buying Gambir Tea with a t value of 6.343 and an r table of 1.666, so Ho3 is rejected and Ha3 is accepted. So it can be concluded simultaneously that Price, Brand Awareness and Product Quality influence buying interest in Gambir Tea.